The Effect of Work-Life Balance and Career Development on Employee Performance - Rolland Fanggidae; Christin Febianti; Clarce Sarliana Maak (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aims to (1) describe work-life balance, career development, and employee performance at PT. National Pension Savings Bank (BTPN) Kupang Branch (2) significant effect of work-life balance on employee performance at PT. National Pension Savings Bank (BTPN) Kupang Branch (3) significant influence of career development on employee performance at PT. National Pension Savings Bank (BTPN) Kupang Branch (4) the effect of work-life balance and development on the performance of employees of PT. Kupang branch of the National Pension Savings Bank (BTPN). There were 36 samples in this study which were obtained using the Slovin formula and the sampling technique used random sampling technique. The data analysis method used is quantitative analysis using validity and determinant coefficient tests. The results of the research using descriptive analysis using a range of scores for the work-life balance variable are in the very high category, while career development and employee performance are in the high category. Work-life balance partially affects employee performance, career development partially affects employee performance, and work-life balance and career development simultaneously affect employee performance.